2019
DOI: 10.1021/jacs.9b00925
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to Bridged Ring Systems via Point-to-Planar Chirality Transfer: Unified Synthesis of Ten Cyclocitrinols

Abstract: Bridged ring systems are found in a wide variety of biologically active molecules including pharmaceuticals and natural products. However, the development of practical methods to access such systems with precise control of the planar chirality presents considerable challenges to synthetic chemists. In the context of our work on the synthesis of cyclocitrinols, a family of steroidal natural products, we herein report the development of a point-to-planar chirality transfer strategy for preparing bridged ring sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 121 publications
1
21
0
Order By: Relevance
“…To test if the rearrangement to the di abeo ‐structures could be initiated without employing toxic Hg or Pb reagents, 22 was treated with Ag 2 O and I 2 . However, only elimination of the 14‐hydroxyl was observed (to give 28 ) along with partial i ‐steroid opening to give iodide 27 as a mixture of epimers (5α/5β 2.3:1) . Knowles’ photocatalytic ring expansion conditions either did not yield any rearranged product but resulted in the isolation of Δ 8, 14 ‐steroid 29 .…”
Section: Resultsmentioning
confidence: 99%
“…To test if the rearrangement to the di abeo ‐structures could be initiated without employing toxic Hg or Pb reagents, 22 was treated with Ag 2 O and I 2 . However, only elimination of the 14‐hydroxyl was observed (to give 28 ) along with partial i ‐steroid opening to give iodide 27 as a mixture of epimers (5α/5β 2.3:1) . Knowles’ photocatalytic ring expansion conditions either did not yield any rearranged product but resulted in the isolation of Δ 8, 14 ‐steroid 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Li's Total Synthesis of (+)-Cyclocitrinol (2018) Cyclocitrinol (56, Figure 8) was first isolated in 2000 by Grafe and coworkers from terrestrial Penicillium citrinum. 69,70 More than 25 diverse cyclocitrinols have been isolated, 71 some of which can induce the production of cAMP in GPR12-transfected CHO cells at low concentration (10 mM). Structurally, cyclocitrinol is composed of a sterically compact 7/7/6/5 tetracyclic skeleton with a unique bicyclo[4.4.1]undecene A/B ring system and a strained bridgehead double bond, which presents a formidable synthetic challenge.…”
Section: Type II [5+2] Cycloadditionmentioning
confidence: 99%
“…The next task was to prepare the cyclopropane moiety in 108 and investigate the biomimetic cascade rearrangement. Eventually, the authors identified that sulfoxides 107 could hypothetically be converted into desired triene 111 through carbocation intermediates 71 108 and 109 via path a in 54% yield in the presence of O-methylquinine with heating. The cyclopropane fragmentation product obtained through path b was also isolated in 11% yield.…”
Section: Rearrangement Biomimetic Cascade Rearrangementmentioning
confidence: 99%
“…Batrachotoxin is a steroidal alkaloid with neurotoxic properties isolated in 1968 from the skin of Columbian poison‐arrow frogs Batrachotoxin features multiple fused rings and high level of skeletal oxidation and represents a formidable synthetic target. [7k], In 2018 Inoue's group disclosed a new approach that allowed for the synthesis of batrachotoxin's steroidal core 110 (Scheme ), which could potentially be expanded to the synthesis of batrachotoxin . Intermediate 110 was generated from 111 through the intramolecular Pd/Ni‐catalyzed Ullman coupling reaction.…”
Section: Syntheses Enabled By Transition Metal Catalysismentioning
confidence: 99%
“…It is primarily focused on the studies that have emerged since 2014 and that have not been reviewed elsewhere . This Minireview does not cover some of the important advances in closely related areas of asymmetric non‐steroidal terpene natural product syntheses , …”
Section: Introductionmentioning
confidence: 99%